+0  
 
0
353
3
avatar

(2x+1)/(x^(2)-1)+(x)/(x^(2)-3x+2)=4

Guest Jul 16, 2017
 #1
avatar+93627 
+2

(2x+1)/(x^(2)-1)+(x)/(x^(2)-3x+2)=4

 

I'll try and make sense of your question first

 

\(\frac{(2x+1)}{(x^{2}-1)}+\frac{(x)}{(x^{2}-3x+2)}=4\qquad x\ne\pm1\\ \frac{(2x+1)}{(x-1)(x+1)}+\frac{(x)}{(x-2)(x-1)}=4 \qquad x\ne\pm1,\quad x\ne2\\ \frac{(2x+1)(x-2)}{(x-1)(x+1)(x-2)}+\frac{(x)(x+1)}{(x-2)(x-1)(x+1)}=4\\ (2x+1)(x-2)+(x)(x+1)=4(x-1)(x+1)(x-2)\\ 2x^2-4x+x-2+x^2+x=4(x-1)(x+1)(x-2)\\ 3x^2-3x+x-2=(x-2)(4x^2-4)\\ 3x^2-2x-2=4x^3-4x-8x^2+8\\ 0=4x^3-4x+2x-8x^2-3x^2+8+2\\ 0=4x^3-11x^2-2x+10\\ \)

 

Here is the approximate answers

https://www.wolframalpha.com/input/?i=4x%5E3-11x%5E2-2x%2B10%3D0

Melody  Jul 16, 2017
 #2
avatar
+1

Thank you. I'm having doubts about my answer but now I see where I am wrong

Guest Jul 16, 2017
 #3
avatar+27035 
+2

This should help you visualize the equation:

 

.

Alan  Jul 16, 2017

15 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.